Effect of varying levels of dietary ochratoxin A on the performance of broiler chickens - SINGH, RAM; MANDAL, A B; SHARMA, MAMTA; BISWAS, AVISHEK (The Indian Journal of Animal Sciences, 2015)
In the present study, the effect of varying levels of ochratoxin A (OTA) in the diet of broiler chickens was investigated. Day-old broiler chicks (200) were divided into 5 treatment groups (T1- control; T2 - T1 + 100 ppb OTA; T3 - T1 + 200 ppb OTA; T4 - T1 + 300 ppb OTA; and T5 - T1 + 400 ppb OTA. Each diet was fed to 4 replicated groups of 10 birds each from day- old to 42 days of age. During overall growth period (0-6 weeks), body weight gain (BWG) in T3, T4 and T5 was significantly lower than that of control group, whereas, the BWG of group T2 was statistically similar to that of control. OTA contamination at 200 ppb or higher resulted in significant reduction in BWG of broiler chicken. The overall feed intake (FI) in T5 was significantly lower than that of control group (T1). The FI in groups T2, T3 and T4 was statistically similar to that of control. OTA contamination at 200 ppb or higher resulted in poor FCR and thus deteriorating feed utilization efficiency in broilers. OTA at 200 ppb or at higher level resulted in increased mortality. Addition of 100 ppb OTA in diet did not produce any change in relative weights of liver, kidney and bursa of Fabricius, however, OTA contamination at 200 ppb or higher resulted in increased relative weights of liver and kidney; and reduced relative weight of bursa of Fabricius. Inclusion of 100 ppb OTA in diet did not produce any change in biochemical parameters of broiler chicken also. It was concluded that ochratoxin A up to 100 ppb in diet had no adverse effect on growth performance, organ weight and certain biochemical parameters in broiler chicken.